Penegakan Hukum Pidana Terhadap Tindak Pidana Kekerasan Seksual di Perguruan Tinggi Pasca Berlakunya Permendikbudristek Nomor 30 Tahun 2021 - Nurul Lisa Andriani; Aroma Elmina Martha (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research has the background of criminal law enforcement efforts against criminal acts of sexual violence that occur in the university environment after the enactment of Permendikbudristek Number 30 of 2021. The approach method used is to use a case and statutory approach. This study discusses what causes sexual violence in higher education, what obstacles are faced by the PPKS Task Force and the efforts made by the PPKS Task Force in resolving sexual violence in higher education. This study aims to determine how the practice of criminal law enforcement against criminal acts of sexual violence in higher education after the enactment of Permendikbudristek Number 30 of 2021 because there are complaints that students are victims of sexual violence but the university is slow in handling the case. Victims are entitled to legal protection so that universities that have not formed the PPKS Task Force are expected to immediately form, and enforce Permendikbudristek Number 30 of 2021 by conducting surveys every 6 (six) months to minimize the occurrence of sexual violence in higher education.